Analysis Of Poverty Reduction Concepts And Strategies From An Islamic Economic Perspective - Widia Sukra; Meisy Melani; Iiz Izmuddin (Universitas 17 Agustus 1945 Semarang, 2024)
Poverty is a common problem for developing countries, especially to improve the welfare of their citizens. With various programs and policies being pursued with the aim of reducing poverty. Islam really wants its people to have a decent life and receive blessings in life and the afterlife. This means that Islam really wants its people to achieve prosperity. In this paper, the method used is descriptive qualitative which aims to describe regularly and factually. This research comes from literature such as books, journals and articles related to research. The findings of this research are that Islam views poverty not only as a social problem, but also as having spiritual and religious implications. One of the efforts to overcome poverty is environmental empowerment and entrepreneurial empowerment. The strategy for alleviating poverty that can be carried out from an Islamic economic perspective is by developing an economy based on zakat, cooperatives, education, health and transportation.